Using Project Work to Strengthen Thai Students’ Learning Attitude toward English Language - et. al., Abigail M. Essien, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The practical significance of this research relates to assisting the students to develop interest in learning English, improve students’ speaking skill and the method by which English lessons are delivered in Thai schools. This study aims to (1) utilize Project Work to strengthen Thai students’ learning attitude toward English language; (2) outline Thai students’ perceptions toward Project Work; and (3) observe the impact of Project Work on Thai students’ speaking ability. The study employs qualitative research style by using (1) students’ learning attitudes observation form; (2) students’ perception of Project Work-Based Learning questionnaire form; and (3) students’ English speaking ability observation form. The subjects consist of 57 4th year pre-service English teachers at Suan Sunandha Rajabhat University (SSRU). The findings unfold that the participants’ learning attitude toward English significantly strengthened while engaging in a Project Work-Based Learning. Learners complete and submit tasks on time; respond and participate in the activities on a rating scale of 4 indicating an excellent attitude. The data also shows that 93% of the respondents are satisfied that Project Work-Based Learning helped improve their English-speaking ability and interest in learning English. Furthermore, the data from the speaking ability observation form discloses that 79% of the subjects’ speech is generally fluent, with occasional lapses while searching for the correct manner of expression; 12% is fluent and effortless and near to that of a native speaker. Therefore, this study highly recommends the implementation of PBL to improve students’ speaking ability and learning attitude toward English.